PENYULUHANMOTIVASIKEWIRAUSAHAANUNTUKPARAREMAJA - Sarastri Mumpuni (Asian Journal of Innovation and Entrepreneurship, 2013)
Unemployment is increasing if not controlled it will make people potentially in thenegative direction. Therefore, it takes the entrepreneurial spirit for every human beingto reduce the number of unemployed. From the observations that have been made, weget information about the work of the youth in the village of Karang. Adolescents whowere in the hamlet of Coral majority do not have a permanent job. Most of them arestill working odd jobs, some work by others and some are just helping parents work inthe fields, gardens and fish ponds. There are even some who really do not have a job.The teenagers in the village of Karang still very few who become entrepreneurs. And aswas said by one of the teenagers in the village of Karang that teenagers in the village ofKarang no one dared try to be an entrepreneur until he actually resorted to new hewould be an entrepreneur. They prefer to work that gets results that remain forexample such as being a security guard who earn a salary every month. The purpose ofthis work program is the emergence of a new desire and passion to become a successfulentrepreneur. The stages of the activities carried out during ongoing counseling anddebriefing seminars, sharing of experience, film screenings. The program is implementedproperly and received a positive response from the community. Once the program isthe youth are motivated and have the passion to become a successful entrepreneur.